2019
DOI: 10.21037/atm.2019.11.18
|View full text |Cite
|
Sign up to set email alerts
|

Isoquercitrin promotes peripheral nerve regeneration through inhibiting oxidative stress following sciatic crush injury in mice

Abstract: Background: Oxidative stress has been recognized to play a crucial role in the pathogenesis of peripheral nerve injury. Isoquercitrin (quercetin-3-glucoside) is a flavonoid that exhibited many biological activities, including antioxidative effect. However, it is unclear whether isoquercitrin has protective effects on peripheral nerve injury.Methods: Mice treated by isoquercitrin were used as a case group, and mice injected with saline was the control group. Sciatic behavioral function was assessed using SFI an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 55 publications
1
25
0
Order By: Relevance
“…37,38 For example, isoquercitrin treatment significantly increases the production of GAP43, NF200, MAG, and PMP22, and promotes the nerve regeneration and remyelination. 39 Our results revealed that UTI administration increased the expression of these markers, which suggested that UTI promoted the functional recovery of peripheral nerve by facilitating the axonal outgrowth and remyelination.…”
Section: Discussionsupporting
confidence: 52%
“…37,38 For example, isoquercitrin treatment significantly increases the production of GAP43, NF200, MAG, and PMP22, and promotes the nerve regeneration and remyelination. 39 Our results revealed that UTI administration increased the expression of these markers, which suggested that UTI promoted the functional recovery of peripheral nerve by facilitating the axonal outgrowth and remyelination.…”
Section: Discussionsupporting
confidence: 52%
“…First, IQC treatment ameliorated the excessive reactive oxygen species production, and exacerbated the anti-oxygen activity (superoxide dismutase and catalase modulation) in vivo and in vitro after ischemia/reperfusion (Dai et al, 2018). According to a report, IQC promoted peripheral nerve regeneration following nerve injury through suppress of oxidative stress in mice (Qiu et al, 2019). Furthermore, IQC exerted a protective part in apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there are also other agents applied for treatment of PNI. For instance, quercetin induces neurite growth by promoting GAP-43 expression [ 37 ], and isoquercitrin promotes peripheral nerve regeneration and remyelination after sciatic crush injury in mice [ 38 ]. The effects of GTPs on peripheral nerve regeneration and remyelination are similar to those of isoquercitrin.…”
Section: Discussionmentioning
confidence: 99%